Working the Crowd : Social media marketing for business. - Brown, Eileen (British Informatics Society, 2012)
Engaging with social media such as Facebook, Twitter, blogs and social news sites is now a key part of global business communications. This book is an excellent resource for anyone planning a social media strategy or individual campaign . The new edition covers the latest thinking, practices and technology such as Google+.